The value of Stilbestrol in the fattening ration of beef steers. - Richardson, D.; Mackintosh, D.L.; Wheat, J.D.; Menzies, C.S.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
The addition of stilbestrol to a high-energy fattening ration has consistently demonstrated its ability to increase rate of gain with older or heavier feeder cattle. At the time this test was initiated, there was considerable confusion as to the effect of stilbestrol upon carcass quality. This cooperative test with large numbers of cattle was conducted to obtain further information on rate and efficiency of gain and the effect upon carcass quality.
Keywords: Beef; Stilbestrol; Gain; Carcass quality